pelling ability and its relationship to reading comprehension among fifth grade primary students (Journal of the College of Basic Education, 2022)
The research aims to identify (spelling ability and its relationship to reading comprehension among fifth-grade primary students) and to verify the aim of the research, the researcher adopted the descriptive approach, studying the relationships as the appropriate approach to the nature of the research, the research community consisted of government day primary primary schools affiliated to the General Directorate of Education in Baghdad, the third Rusafa, and consisted The research sample consists of (200) male and female students, by (104) male and (96) male and female students. The research sample was chosen in a stratified random manner. The researcher prepared a test of the spelling ability, as it included (25) paragraphs, and the researcher chose the objective test and the higher degree was (25) ) And minimum (Zero), and the researcher confirmed the validity and reliability of the tools. The researcher also prepared a reading comprehension test and included (31) paragraphs of type (multiple choice, filling in the blanks, linking between sentences and their meanings, and replacing words). The higher grade was (31) and the minimum (zero) The researcher used the following statistical methods: (the Fakronbach equation, the difficulty factor, the discrimination factor, the effectiveness of the wrong alternatives, the Pearson correlation coefficient), and the results of the research resulted in the following: There is a correlative (direct) relationship among students between the spelling ability test and the reading comprehension test, in light of the research results, the researcher recommends the need to increase and include Arabic reading books in the primary stage, especially the fifth grade, some short and easy pieces that include the spelling ability represented by (spelling skills) and absorption skills Readers to train students to acquire, acquire and develop them, and the researcher suggested conducting a study on another stage and other variables and branches.